2020
DOI: 10.3389/fnmol.2020.602559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GABAA Receptor α3 Subunit Epilepsy Mutations on Inhibitory Synaptic Signaling

Abstract: Missense mutations T166M, Q242L, T336M, and Y474C in the GABAA receptor (GABAAR) α3 subunit gene are associated with epileptic seizures, dysmorphic features, intellectual disability, and developmental delay. When incorporated into GABAARs expressed in oocytes, all mutations are known to reduce GABA-evoked whole-cell currents. However, their impact on the properties of inhibitory synaptic currents (IPSCs) is unknown, largely because it is difficult to establish, much less control, the stoichiometry of GABAAR ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…On the other hand, IPSC amplitude was dramatically suppressed, and the suppression was greater in the late post-PNI period. The decay time of IPSC has been shown to be highly dependent on GABA receptor isoforms, 37 and chronic pain is accompanied by altered expression of some GABA receptor subunits, 38 and our results support these reports. One of the main reasons why our results differ from previous electrophysiological reports of inhibitory synaptic transmission after PNI is the difference between in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, IPSC amplitude was dramatically suppressed, and the suppression was greater in the late post-PNI period. The decay time of IPSC has been shown to be highly dependent on GABA receptor isoforms, 37 and chronic pain is accompanied by altered expression of some GABA receptor subunits, 38 and our results support these reports. One of the main reasons why our results differ from previous electrophysiological reports of inhibitory synaptic transmission after PNI is the difference between in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, key phenotypic differences may even be seen between individuals with the same genetic alteration [ 71 ]. In a recent study on GABRB3 variants, it was reported that there was a significant genotype–phenotype correlation in individuals affected by GABRB3 -related disorders, as they were clustered in three regions of the β3 subunit that were key to its function (GABA binding region, coupling region, and TMD) [ 72 ], clearly linking GABR variant pathogenicity and receptor structure–function [ 29 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two of these genes, CACNA1C and GABRA3, harbored high impact de novo and hemizygous missense variants respectively, corresponding to known patient diagnoses. 55,56 The genome of another, undiagnosed, now deceased patient from this cluster with no prior candidate variants contained a synonymous de novo variant predicted to alter splicing in another gene in the same functional pathway, HCN4 (Figure 4d). All three patients exhibited seizures at a young age, speech delays, severe hypotonia, spasticity and visual impairment.…”
Section: Introductionmentioning
confidence: 99%